Забезпечення метрологічної надійності вимірювань - Володарський, Є. Т.; Потоцький, І. О.; Volodarsky, Eugen; Pototskiy, Ihor (Видавництво Львівської політехніки, 2019)
У статті запропоновано підхід щодо дослідження метрологічної надійності вимірювань з урахуванням умов та режимів функціонування засобів вимірювальної техніки, оснований на проміжному контролі середньо- квадратичного відхилення результатів вимірювань. Введено нове поняття критичної послідовності точок на контрольній карті Шухарта (s-карті), поява якої свідчить про наявність впливу на результат вимірювання засобом вимірювальної техніки невипадкових величин. Проаналізовано ймовірності потрапляння послідовностей точок у певні діапазони контрольної карти, відповідно до закону розподілу середньоквадратичного відхилення, на основі яких запропоновано критерії встановлення необхідності калібрування або ремонту засобу вимірювальної техніки.

The article proposes an approach to the research of the metrological reliability of measurements taking into account the conditions and operating modes of measuring equipment, based on the intermediate control of the standard deviation of the measurement results. The above approach is relevant because it allows laboratories to reasonably set the recalibration intervals of measuring equipment based on the control of standard deviations. The requirement for reasonable setting of recalibration intervals for measuring instruments is a common worldwide practice. A new concept of the critical sequence of points on the Shewhart control chart (s-chart) was introduced, the appearance of which indicates the presence of non-random variables of the measurement result by the measuring equipment. The probabilities of point sequences falling into certain ranges of the control chart are analyzed based on the law of distribution of standard deviation. It is proposed to subdivide the whole interval of probable hit of the standard deviation checkpoints on the Shewhart control chart for research purposes. Subsequently, a situation where a certain number of consecutive points falls within one or another range (or several adjacent ranges) was simulated, and it was proved that the occurrence of such critical points sequences on the control chart could indicate a loss of metrological reliability of the measuring instrument. To clarify the information, the article presents graphs of the probability of complex events (certain sequences of points) on the number of consecutive control points in the distribution ranges. The analysis made it possible to propose the criteria for establishing the need for calibration or repair of the measuring equipment, based on the results of intermediate checks and control of the standard deviation.
Methodical error of targets bearing by sound artillery intelligence system
Keywords: метрологічна надійність; вимірювання; міжкалібрувальний інтервал; контрольна карта; середньоквадратичне відхилення; Metrological reliability; Measurements; Recalibration interval; Control chart; Standard deviation